African economic outlook 2009 : country notes : a companion volume to African economic outlook 2009 : overview. Volume 1 - African Development Bank; Organizace pro ekonomickou spolupráci a rozvoj. Development Centre (Paris : Organisation for Economic Co-operation and Development, 2009)
This fact-filled annual reference book brings the reader the latest available economic information for most of the economies of Africa. Drawing on the expertise of both the African Development Bank and the OECD, it opens with an overview that examines the international environment, macroeconomic performance, progress towards attaining the Millennium Development Goals, and governance and political issues. The second part provides individual country reports for 30 countries. Each country report provides an assessment of recent economic performance, economic projections, an examination of structural issues, and a discussion of the political and social context. The statistical annex presents 24 tables comparing economic and social variables across all the countries of Africa
Pod názvem: African Development Bank, Development Centre of the Organisation for Economic Co-operation and Development
Keywords: ekonomický růst; ekonomické ukazatele; hospodářská politika; Afrika; hospodářský vývoj; studie; economic development; economic indicators; economic policy; Africa; studies